Resiliensi Muslim Moderat di Era Post Truth: Tipologi, Teori dan Praktik Di Indonesia - Huda, M Syamsul; Irama, Yoga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This article aims to examine the resilience of moderate Muslims in the midst of the reality of the post truth virus that has spread today. The purpose of this research is to find out the typology, theory and practice of moderate Islam in the post-truth era in Indonesia. The approach used is qualitative and by using descriptive analysis methods to study various data sources: from books, journals, scientific works, newspapers, and so on that have a relationship with the theme of discussion. The results of the study show that the typology of moderate Islam refers to those who reject the application of violence as a line of ideology and struggle. The theory of moderate Islam or wasatiyyah Islam has emerged and developed in three historical periods: 1) the ta'sis period (the formation period); 2) tathwir period (development period); 3) the period of tahdits (modernization). The practice of moderate Islam or wasatiyyah Islam in the post-truth era is fused into three scopes of lines of action, including: 1) epistemological lines, moderate Islam is not only inclined to one methodological door in obtaining the truth, but uses various sides of approach to obtain factual truth, so it is less likely to be exposed to hoaxes in the post truth era; 2) the ontological line, the existence of Islamic wasatiyyah is also a response to cases of stigmatizing Islamophobia in Indonesia; 3) the axiological line, the dimensions of wisdom and wisdom values wrapped in the concepts of tasamuh (tolerance), ta'adul (fair), tawazun (balanced) in moderate Islam, are very effectively applied in the post truth era to fight hoaxes and doctrines of extremist acts that terrorist groups continue to do today.